Radiofrequency ablation can reverse the structural remodeling caused by frequent premature ventricular contractions originating from the right ventricular outflow tract even in a normal heart (Clinics, 2013)
OBJECTIVE: The aim of this study was to evaluate whether frequent premature ventricular contractions originating from the right ventricular outflow tract remodel the cardiac structure and function in patients with a “seemingly normal heart” and whether radiofrequency ablation can reverse this remodeling. METHODS: Sixty-eight patients with idiopathic frequent premature ventricular contractions originating from the right ventricular outflow tract and normal heart structure and function were enrolled in this study. The patients were divided into three groups according to the therapeutic method: radiofrequency ablation group (24 cases), anti-arrhythmia drug group (26 cases), and control group (18 cases without any treatment). Clinical Registration number: ChiCTR-ONRC-12002834 RESULTS: The basic patient characteristics were comparable between the three groups, except for the premature ventricular contraction rate, which was significantly lower in the control group. After six months of follow up, the premature ventricular contraction rate was significantly reduced in the radiofrequency ablation group, which was accompanied by a significant decrease in the following cardiac cavity inner diameters, as determined by echocardiography: right atrium (33.33±3.78 vs. 30.05±2.60 mm, p = 0.001), right ventricle (23.24±2.40 vs. 21.05±2.16 mm, p = 0.020), and left ventricle (44.76±4.33 vs. 41.71±3.44 mm, p = 0.025). These results were similar in the anti-arrhythmia drug group, although this group exhibited a smaller extent of change (right atrium: 33.94±3.25 vs. 31.27±3.11 mm, p = 0.024; right ventricle: 22.97±3.09 vs. 21.64±2.33 mm, p = 0.049; left ventricle: 45.92±6.38 vs. 43.84±5.67 mm, p = 0.039), but not in the control group (p>;0.05). There was a tendency toward improvement in the cardiac functions in both the radiofrequency ablation and anti-arrhythmia drug groups. However, these differences were not statistically significant (p>;0.05). CONCLUSIONS: These results indicate that radiofrequency ablation can potentially reverse the cardiac remodeling caused by frequent premature ventricular contractions even in structurally normal hearts and that frequent premature ventricular contractions should be abated even in structurally normal hearts.